A field-induced hole generation layer for high performance alternating current polymer electroluminescence and its application to extremely flexible devices. Issue 20 (15th April 2016) - Lee, Ju Han; Cho, Sung Hwan; Kim, Richard Hahnkee; Jeong, Beomjin; Hwang, Sun Kak; Hwang, Ihn; Kim, Kang Lib; Kim, Eui Hyuk; Lee, Tae-Woo; Park, Cheolmin
Abstract : An extremely flexible AC-PEL device was developed with doped PEDOT:PSS. Abstract : The performance of alternating current driven electroluminescent devices significantly depends on the total amount of injected carriers as well as the balance of the number of injected carriers in an emission layer, which requires a careful design of the relative energy level structures of constituent layers. Here, we demonstrate a new field-induced hole generation layer between an emission layer and an insulator for high performance alternating current polymer electroluminescence (AC-PEL). Our hole generation layer of doped poly(3, 4-ethylenedioxythiophene)–poly(styrene sulfonate) in the presence of multi-walled carbon nanotubes was also able to supply sufficient holes, giving rise to a good balance with the number of electrons readily injected from a top electrode. The resulting AC-PEL device exhibits high electroluminescence performance with a low turn-on root-mean-square voltage of 8.8 Vrms, a maximum luminance of 40 919 cd m −2, a maximum current efficiency of 3.74 cd A −1 and a power efficiency of 3.25 lm W −1 . Other buffer layers such as WO3 and MoO3 are also suitable as field-induced hole generation layers. Moreover, our hole generation layer enables us to develop an extremely flexible and even foldable AC-PEL device when combined with a polymer insulator as well as a flexible transparent electrode based on the Ag nanowire network.